2022
DOI: 10.1155/2022/1177745
|View full text |Cite
|
Sign up to set email alerts
|

Rock Crushing Analysis of TBM Disc Cutter Assisted by Ultra-High-Frequency Loading

Abstract: In the construction of mountain tunnels, the increasing proportion of hard rock stratum enhances the difficulty of rock breaking by tunnel boring machine (TBM). As a type of cyclic load with ultrahigh frequency, ultrasonic vibration has the advantages of energy concentration and strong penetration. In the process of rolling and extrusion, the weakening of the rock by ultrahigh-frequency loading can improve the rock crushing efficiency of the TBM disc cutter. In this study, we established a physical model of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Zhao et al [25] used particle flow discrete element software to simulate the ultrasonicvibration-assisted hob rock-breaking process. They found that ultrasonic waves contribute to the tensile damage of shallow rock, enhance the scale of crack generation within rock, accelerate the crack generation rate, advance the time of the initial development of cracks, and have a good gain effect on a hob's rock-breaking performance.…”
Section: Overview Of Ultrasonic High-frequency-vibration Rock-breakin...mentioning
confidence: 99%
“…Zhao et al [25] used particle flow discrete element software to simulate the ultrasonicvibration-assisted hob rock-breaking process. They found that ultrasonic waves contribute to the tensile damage of shallow rock, enhance the scale of crack generation within rock, accelerate the crack generation rate, advance the time of the initial development of cracks, and have a good gain effect on a hob's rock-breaking performance.…”
Section: Overview Of Ultrasonic High-frequency-vibration Rock-breakin...mentioning
confidence: 99%